Blood flow pattern in eye before development of type 3 macular neovascularization - Yamaguchi, Saya; Maruko, Ichiro; Maruko, Ruka; Hasegawa, Taiji; Iida, Tomohiro (PloS one, 2023)
To determine the blood flow pattern of eyes before the development of type 3 macular neovascularization (MNV) by optical coherence tomography angiography (OCTA). Retrospective study. Ten eyes of 10 patients (4 men and 6 women, mean age 80.4 years) diagnosed with unilateral Type 3 MNV who developed type 3 MNV in the fellow normal eye during the follow-up period were studied. The time of onset of type 3 MNV was defined as the time when retinal exudation was detected by OCT. The blood flow of a 3 x 3 mm or 6 x 6 mm area in the deep capillary plexus (DCP) and the outer retina (OR) including the central fovea were assessed at the onset and at 6 months prior to the onset of the type 3 MNV. All MNVs that developed in the fellow eye were type 3 MNVs. Abnormal blood flow signals in the MNVs were detected in the DCP and/or the OR by OCTA at the onset in all cases. Eight of the 10 eyes had OCTA recordings prior to the development of the MNV: 3 eyes had non-exudative MNVs only in the DCP and 5 eyes had non-exudative MNVs in the DCP and OR. The exudation appeared on the average 3.5 months after the non-exudative MNV was observed in the fellow eyes. A non-exudative MNV in the fellow eyes can already be observed by OCTA in eyes before the onset of the exudation. Knowing this will help clinicians not only how to treat these eyes appropriately but will also help in determining the origin of the MNV.